An Analysis of the Translation of a Scientific Article entitled Fiction from the Periphery: How Dutch Writers Enter the Field of English Language Literature - Rinta Sukma Firdaus, Mei; Widyasari (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Literary translations throughout the world are mostly made from English, so a translator is needed to translate into other languages. Translation is defined as the process of transferring a source language message (TL) into the target language (TL) in an equivalent manner. Translation of the journal entitled "Fiction from the Periphery: How Dutch Writers Enter the Field of English Language Literature” discusses the analyzes carried out in translation, the translation methods and techniques applied. This analysis focuses only on Chap Fiction from the Periphery: Implications of the Dutch Case. The application of translation methods and techniques is used to produce reasonable, clear and appropriate translation. This article determines by what mechanisms Dutch writers overcome the obstacles they encounter at the macro, meso, and micro levels. This draws on sociological understandings of how writers from peripheral countries can enter internationally dominant centers, suggesting that such understandings are part of the same theoretical approach that explains the much more frequent flow from centers to peripheral countries.